The marine litter issue in the Windward Islands- a pathway to responses using the DPSIR framework - Graham, Roxanne E. D. (Frontiers in Environmental Science, 2023)
Marine litter is an important and worldwide concern that should be deeper analysed. It also requires information from all over the world and especially in less studied areas like small islands developing states e.g., the Windward Islands of the Eastern Caribbean. This study analyses the issue of marine litter in the English-speaking Windward Islands using the Driver-Pressure-State-Impact-Response (DPSIR) framework. The research is based on a bibliographical review and analysis of scientific and grey literature regarding these islands and the Wider Caribbean Region at large. The Windward Islands present a unique situation because of their geographic location in the south-eastern Caribbean, socio-economic status, and strong external influences. The DPSIR Framework was used to frame and assess the major types, causes and effects of marine litter for the Windward Islands by reviewing current scientific and grey literature. The major solid waste item retrieved from the coastal and marine environment is fishing gear in the case of Dominica and plastic waste for the other islands. The challenges in current and proposed management measures were identified. Proposed solutions in the form of responses were tailored to meet each casual and effect component of the DPSIR framework. The study strongly recommends that the islands make use of their existing participation in global agreements and initiatives, participate more actively in the negotiations for the upcoming Global Plastics Treaty set to launch in 2024, and tackle their mutual need for effective solid waste management systems and infrastructure and increased recycling efforts or opportunities. These measures could undoubtedly pave a way to the achieving a cleaner and healthier ocean.